Infrared Studies On Thermally Stabilized Polyacrylonitrile (PAN) Fiber - Rahaman, M. S. A.; Ismail, A. F.; Mustafa, A.; Ng, B. C.; Abdullah, M. S.; Rahman, M. A.; Hasbullah, H. (2004)
This study reports the investigation of the fiber when subjected to heating process in the temperature range of 200-300 C. This was conducted under atmospheric condition with heating rate as low as 1C/min. The structure of PAN fiber especially the nitrile group (C=N) changed significantly with time and heating temperature. A new peak around 1600 cm-I wavenumber, which represented the double bond structure (C=N) was observed. That triple bond of nitrile group had been eliminated when the final heating temperature reached 300 "C. In addition, high soaking time could help to accelerate the changes in the PAN fiber structure. This study also found that, regardless of the duration of soaking time, the stabilization of PAN fiber can still be stabilized at 300 C .